Maritime autonomous surface ships (MASS) in Gulf of Suez: safety of navigation precautionary measures - Amr Samir Nossir; Samy Isamil A. M. Youssef; Mohamed Essallamy (Maritime Research and Technology)
Abstract  The effects of automation on human safety and environmental protection are generally acknowledged. Maritime Autonomous Surface Ships (MASS) improvements may help eliminate human error and greatly increase overall safety, but they are also likely to pose new threats, particularly given the marine industry's growing interest in MASS. Using a questionnaire, we determined that "communication with human-operated ships" poses the greatest threat to the success of MASS operations, followed by "the threat of cyber-attacks," "the human factor," and "equipment failure." According to our findings, this study sheds light on the impact of MASS on education and training, as well as the most serious threats posed by MASS to the safety of navigation and the marine environment in the Gulf of Suez, and proposes a process, requirements, and legislation for MASS transit in the Gulf of Suez.   Received: 01 September 2022 Accepted: 27 September 2022 Published: 05 January 2023